A method for single frame detection of infrared dim small target in complex background. (September 2020) - Xu, Yongli; Wang, Weihua
Abstract: In order to solve the problem of high false alarm rate caused by strong disturbance (the ground objects, uncertain strong noise) in complex background, we propose a novel algorithm based on density peaks searching and improved region growing. Initially, density peaks searching is employed to select the candidate targets quickly; then, improved region growing with introducing the relative local contrast and the local gray average is used to extract the features of candidate targets; finally, an adaptive threshold is applied to extract real targets. Experimental results on two real sequences show that the proposed algorithm has a better effectiveness against existing algorithms.